Effect of Shredded Waste Paper on Properties of Concrete - Solahuddin, Azuwa; Fadzil, Mat Yahaya (IOP Publishing, 2021)
Cement, sand, coarse aggregate and water are the materials to make a concrete mixture. The waste paper has been dumped as waste and causes environmental pollution behind the mill or landfill. The industry paper wastage for every year is increasing gradually. More spaces are being needed for landfills, uses energy loss of natural resources and increase of expenditure and various types of pollutions. Utilizing waste paper as an addition in concrete production will reduce environmental pollutions. This research is conducted to investigate the effect of shredded waste paper using copier and cardboard waste paper as additions to the compressive and flexural strengths and water absorption of hardened concrete. All specimens are subjected to water curing at 7 and 28 days. The results of compressive and flexural strengths increase at 5% and 10% additions of shredded copier and cardboard waste paper at 7 and 28 days of water curing. The finding shows that concrete containing 10% addition of shredded copier and cardboard waste paper exhibit the highest compressive and flexural strengths. For concrete water absorption, the higher water absorption is caused by the higher addition of shredded copier and cardboard waste paper. Furthermore, the results also show that shredded cardboard waste paper has higher strength and water absorption than shredded copier waste paper for all percentages of addition. This study indicates that shredded copier and cardboard waste paper can be used as additional materials in concrete production.